Uphill sprinting load- and force-velocity profiling: Assessment and potential applications - Delaney, J. A.; McKay, B. A.; Radcliffe, J; Benton, D. T.; Samozino, P; Morin, J.-B.; Duthie, G. M. (Journal of Sports Sciences, 2022)
This study aimed to quantify the validity and reliability of load-velocity (LV) relationship of hill sprinting using a range of different hill gradients and to describe the effect of hill gradient on sprint performance. Twenty-four collegiate-level athletes performed a series of maximal sprints on either flat terrain or hills of gradients 5.2, 8.8 and 17.6%. Velocity-time curves were recorded using a radar device. LV relationships were established using the maximal velocity achieved in each sprinting condition, whilst force-velocity-power (FVP) profiles were established using only the flat terrain sprint. LV profiles were shown to be valid (R2 = 0.99) and reliable (TE < 4.4%). For every 1-degree increase in slope, subjects` velocity decreased by 1.7 ± 0.1% on average. All the slopes used represented low resistance relative to the entire LV spectrum (<25% velocity loss). Subjects who exhibited greater horizontal force output at higher velocities on flat terrain were most affected by the gradient of the hill. Hills of gradients up to 17.6% do not provide sufficient resistance to optimize power development. However, such hills could be used to develop late-stage technical ability, due to the prolonged horizontally oriented body position that occurs as subjects attempt to overcome the acceleration due to gravity.